Durability of concrete incorporating crushed brick as coarse aggregate. (30th September 2015) - Adamson, M.; Razmjoo, A.; Poursaee, A.
Highlights: Concrete with brick aggregates showed an increase in its workability. By increasing the brick content, the resistance to chloride penetration decreases. Corrosion of steel in samples with brick aggregates initiated first. Abstract: Using crushed bricks as coarse aggregates in concrete is of particular interest to preserve natural aggregate sources as well as to reduce waste and waste storage. The objective of this experimental work was to study the durability of reinforced concrete made with crushed brick as aggregate. For this purpose, a comparative study was performed on the durability properties of concrete made with crushed brick as coarse aggregates and with natural aggregates. Results show that the natural coarse aggregates can be replaced by crushed bricks, without significant change in the durability of concrete when the steel is not present. However, when concrete is reinforced with steel, replacing natural aggregates with crushed brick is not recommended.